PENGARUH PENDAPATAN DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL SERTA DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI PROVINSI SUMATERA UTARA - Zulaili, Zulaili; Lubis, Porkas Sojuangon; Insy Sinaga, Rini Viri (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aimed to analyze the effect of Regional Generated Revenues (PAD) and General Allocation Fund (DAU) to Capital Expenditure (BM) and their impact on Regional Gross Domestic Product (PDRB) in 33 districts/towns of North Sumatera Province. The data used are secondary data obtained from the Central Statistical Agency (BPS) and the site of Directorate General of Fiscal Balance (www.djpk.depkeu.go.id) of North Sumatera Province for the period of 2010 to 2015. The data were analyzed by using path analysis.The result of the research showed that simultaneously Regional Generated Revenues, General Allocation Fund and Capital Expenditure had impact on economic growth.